Assessment of the Spatiotemporal Evolution Characteristics and Driving Factors of Ecological Vulnerability in the Hubei Section of the Yangtze River Economic Belt - Shuai Wu; Guanzhong Zeng; Jie Sun; Xiaohuang Liu; Xuanhui Li; Qinghua Zeng; Shijie Gu (Land)
The Hubei section of the Yangtze River Economic Belt (YREB) has an important strategic position as the core zone of the central part of the YREB, and the advantages and disadvantages of its ecological environment are closely related to the development quality of the whole YREB. Moreover, the systematic assessment of ecological vulnerability is of great significance to regional ecological environmental protection, the rational exploitation and utilization of resources, and sustainable development. Based on the pressure–state–response–management model, this study analyzes the spatial and temporal evolution characteristics of the ecological vulnerability of the Hubei section of the YREB and its influencing factors using G1–CRITIC–game theory combination weighting, the Theil index, and the Ridge regression model. The results show that from 2010 to 2023, the area was characterized by medium ecological vulnerability, with an average area share of 58.2%; the degree of vulnerability rose and then fell; the ecological environment gradually improved; and there was an overall spatial distribution pattern of high in the central part and low in the east and west. On the trend of vulnerability transformation, 62.2% of the area remained unchanged, 21% of the area shifted to low vulnerability, and 16.8% of the area increased in vulnerability level. The Theil index decreased and then rose, the degree of spatial agglomeration was floating in a “V” shape, and the spatial pattern of vulnerability was essentially the same in the hot- and cold-spot areas. Among the six ecological functional protection zones, the soil preservation function zone exhibited the lowest average ecological vulnerability index (EVI) at 0.371. From 2010 to 2023, the water source conservation function zone demonstrated a significant decline in EVI, while the remaining zones showed a gradual upward trend in EVI. The human disturbance index was the main driver affecting the change in ecological vulnerability, and the pressure layer was the key influence criterion layer. This study can provide a reasonable evaluation model and analytical framework for the scientific and objective assessment of ecological vulnerability.